Metformin and Covid-19: Focused Review of Mechanisms and Current Literature Suggesting Benefit - Ibrahim, Sherehan; Lowe, Jamie R.; Bramante, Carolyn T.; Shah, Surbhi; Klatt, Nichole R.; Sherwood, Nancy; Aronne, Louis; Puskarich, Michael; Tamariz, Leonardo; Palacio, Ana; Bomberg, Eric; Usher, Michael; et al. (Frontiers in Endocrinology, 2021)
Metformin is the first-line medication for type 2 diabetes, but it also has a long history of improved outcomes in infectious diseases, such as influenza, hepatitis C, and in-vitro assays of zika. In the current Covid-19 pandemic, which has rapidly spread throughout the world, 4 observational studies have been published showing reduced mortality among individuals with home metformin use. There are several potential overlapping mechanisms by which metformin may reduce mortality from Covid-19. Metformin’s past anti-infectious benefits have been both against the infectious agent directly, as well as by improving the underlying health of the human host. It is unknown if the lower mortality suggested by observational studies in patients infected with Covid-19 who are on home metformin is due to direct activity against the virus itself, improved host substrate, or both.